Association of tau tangle burden with depressive symptoms in community‐dwelling older adults: A longitudinal study: Neuropsychiatric symptoms as a treatment target: Recent advances by the ISTAART neuropsychiatric symptoms professional interest area. (7th December 2020) - Gatchel, Jennifer R.; Marshall, Gad A.; Locascio, Joseph J.; Yang, Hyun‐Sik; Donovan, Nancy J.; Buckley, Rachel F.; Properzi, Michael J.; Quiroz, Yakeel T.; Rabin, Jennifer S.; Vannini, Patrizia; Amariglio, Rebecca; Chhatwal, Jasmeer P.; et al.
Abstract: Background: Depressive symptoms are thought to be among the earliest behavioral changes in preclinical Alzheimer's disease (AD). However, the association between AD pathology and depressive symptoms in preclinical AD remains poorly understood. In the current study we examined the impact of pathology burden (amyloid‐β and tau) on longitudinal change in depressive symptoms in cognitively unimpaired adults. Method: 252 adults (age: 70.8 ±8.2; 61% females) from the Harvard Aging Brain Study completed annual assessment with the 30‐item Geriatric Depression Scale (GDS) (average follow‐up=5.87 annual visits). All were cognitively normal, without clinically significant depression at study entry (mean GDS=3.19±3.12; range: (0‐16)). All underwent tau ( 18 F‐Flortaucipir) and amyloid‐β ( 11 C‐Pittburgh Compound B) PET at study year 3 or 4 to derive measures of inferior temporal (IT) and entorhinal cortex (EC) tau and cortical amyloid. A mixed model was employed with dependent variable GDS (for each annual study visit), a random intercept and slope for each participant, and fixed predictors: tau (IT or EC, at study year 3/4), cortical amyloid (at year closest to tau), time (time of tau PET), covariates: age, sex, education; and the interaction of predictors with time. Result: Baseline tau burden was associated with increasing GDS over time. In the model with predictor EC tau, EC tau X time was a significant predictor of GDS (β=0.48; t=3.80; 95% CI (0.23, 0.73); p=0.0002). Findings were similar for IT tau:(β = 0.71; t=3.67; 95% CI (0.33, 1.1); p=0.0002). By contrast, amyloid was not a significant predictor of longitudinal GDS in tau models: (β=‐0.14; t=‐1.58; 95% CI(‐0.23, ‐0.08); p=0.11). Conclusion: Baseline tau, but not amyloid, is independently associated with increasing depressive symptoms over time. Future research incorporating longitudinal tau PET and individuals with more severe depressive symptoms is needed to delineate the temporal sequence of rising depressive symptoms and increasing tauopathy in preclinical AD.